Effectiveness of Periodontal Flap Surgery Multimedia Instructional Program Compared to Standard Lecture - Fatemeh Sarlati; Zakieh Zare; Nasim Laiji; Roya Shariatmadar Ahmadi; Omid Moghaddas; Negin Zokaei (Islamic Dental Association of Iran, 2018)
Background and Aim: The aim of this study was to compare the knowledge and skill performance obtained by dental students exposed to two different instructional modalities for periodontal flap surgery: a Computer-Assisted Learning (CAL) multimedia software program and traditional lecture. Materials and Methods: In this experimental study, fifty volunteer fourth-year dental students with similar grade point average (GPA) scores, with the age range of 22 to 27 years, were divided into two groups (n=25). They all completed a pretest. The test group used a multimedia software, while the control group attended a lecture with the same educational content. Immediately after the lecture and after the students of the soft-ware group have finished watching the program, they completed a test consisting of 14 questions. Then, they were all assigned to perform some skills of periodontal flap surgery on an animal model. The performance of each student was assessed using a questionnaire of 13 items. Data were analyzed using independent samples t-test, Fisher's exact test, and Pearson's chi-squared test. Results: There were no differences in prior knowledge between the two groups at the baseline. The software group had a final average exam score of 12.8+1.50, and the lecture group had an average score of 10.24+1.36; the difference was statistically significant (P<0.001). The CAL group had superior performance in some skills related to periodontal flap surgery (9.98+4.63 and 4.26+4.07, respectively; P<0.000). Conclusion: The multimedia software program can be used as an adjunct to traditional education or as a means of self-instruction in teaching periodontal flap surgery techniques.